Adoption of the internet of things in smart vertical farming systems - Thinakaran, Rajermani; Nagalingam, Sarasvathi; Hui, Eng Jing; Ismail, Nurul Halimatul Asmak; Awwad, Samer A B (Review of Computer Engineering Research, 2025)
The vegetable industry is a fundamental part of Malaysia’s agricultural and economic landscape, providing essential food supplies, creating employment opportunities, and contributing to economic growth. However, recent challenges, such as labor shortages in the agricultural sector, have limited the capacity of Malaysian vegetable businesses to meet increasing market demand. This study proposes the Smart Vertical Farming System (SVFS), utilizing the Internet of Things (IoT) as part of a broader ’green revolution’ focused on applying advanced Information and Communication Technologies (ICT) in agriculture. Using a waterfall development framework and a qualitative research methodology, the SVFS was designed to monitor critical agricultural parameters such as soil moisture, light exposure, and ambient temperature. Initial implementation involved cultivating two different vegetable varieties alongside traditional farming methods. Remarkably, after 19 days, the results showed that vegetables grown using the SVFS experienced faster growth rates and increased leaf production compared to those cultivated conventionally. These findings suggest that integrating innovative farming technologies can significantly improve vegetable quality and yield, while also stabilizing market supply to meet consumer needs at competitive prices. This research demonstrates the potential for technological advancements to address pressing issues within the agricultural sector and enhance overall food security in Malaysia.